Effects of globalization on the professional lives of teachers - Bolivar Botía, Antonio (Avances en Supervisión Educativa, 2009)
This paper examines some of the problems associated with how globalization is reshaping the teaacher’s professional lives, focusing on their effect on the crisis in secondary teachers’ professional identity. Globalization, as Ulrich Beck points out, is experienced as a new modernity. School crisis and its professionals is associated with the crisis of modernity. Teaching in the knowledge society involves the following paradox: in loco parentis, restructuring teaching work, individualization and recognition deficits, performativity and professional practice. Finally, it offers some guidelines to reaffirm the role of schools and teachers in the new globalized modernity.